Mock trial: debates order and defendant antecedents - Pilati, Ronaldo; Silvino, Alexandre Magno Dias; Miura, Marco Akira; Caldas, Lucas Soares (Paidéia (Ribeirão Preto), 2010)
Two mock trial studies had the purpose of evaluate the effect of defendant criminal antecedents and the debate order over the juror deliberation. On the first study a factorial design of 2 (debate order) X 2 (defendant antecedent) was conducted and 123 students watched a video mock trial. The results show a sample tendency to find the defendant guilty and the debates order and the defendant profile had no influence on jurors decisions. However, the prosecutor and attorney performance was significantly correlated with the jurors decision making. The second study had the defendant antecedents as the independent variable and was done with the trial presentation with a text transcription. The sample was 54 students. The results demonstrate that defendant profile had no effect over the juror decisions, but the sample tendency was to find the defendant not guilty. Socio-cognitive processes have to be more investigated in future studies.